7th Annual Symposium on Clinical and Pharmaceutical Solutions through Analysis. (October 2016) - Zhang, Tianyi (Tee); Wang, Li; Weng, Naidong; Dong, Kelly; Valaskovic, Gary; Lee, Mike
7th Annual Symposium on Clinical & Pharmaceutical Solutions through Analysis, Renaissance Shanghai Pudong Hotel, Shanghai, China, 20–23 April 2016 The 7th Annual Shanghai Symposium on Innovative Approaches to Reduce Attrition and Predict Clinical Outcomes (CPSA Shanghai 2016) was held on 20–23 April 2016 in Renaissance Shanghai Pudong Hotel, Shanghai, China. The meeting was featured with highly interactive events including diversified symposia, round table discussions, workshops, poster sessions and conference awards. There were over 220 participants from more than ten countries, with 61 oral presentations and 29 posters presented. In addition, the meeting included one preconference workshop and three joint sessions held with bioanalytical experts from local communities.